Mo2CTx two-dimensional material and preparation method and application thereof

Through the hydrothermal reaction method, Mo2Ga2C MAX material is reacted with ammonium fluoride at high temperature to prepare a two-dimensional Mo2CTx material, which solves the safety and environmental protection problems of using strong acids or strong alkalis in traditional methods, and realizes an efficient, safe and environmentally friendly preparation process to meet the needs of large-scale applications.

CN119591110APending Publication Date: 2025-03-11UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411750146.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The traditional Mo2CTx two-dimensional material preparation method has harsh conditions such as the use of strong acids or strong alkalis, which have great safety hazards, great environmental impact, low production efficiency, and difficult to meet the needs of large-scale applications.

Method used

The Mo2Ga2C MAX material was reacted with ammonium fluoride under conditions of 190°C to 240°C to prepare a two-dimensional Mo2CTx material. This method does not require the use of strong acids or strong alkalis, and the hydrothermal temperature is high, which can ensure the safety and efficiency of the reaction.

Benefits of technology

It has achieved efficient preparation of Mo2CTx two-dimensional materials, with high production efficiency, significant improvement in safety and environmental protection, which can meet the needs of large-scale applications and reduce the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the field of nano material preparation, in particular to a Mo2CTx two-dimensional material and a preparation method and application thereof. According to the preparation method of the Mo2CTx two-dimensional material, Mo2Ga2C is etched through a simple one-step hydrothermal reaction, a non-toxic reagent ammonium fluoride is utilized, a MAX precursor is etched on a large scale through a one-step method, the Mo2CTx two-dimensional material is prepared, the preparation process is simple, large-scale production is easy, safety and reliability are achieved, and strong acid, strong base or a chemical intercalator does not need to be introduced; the obtained Mo2CTx two-dimensional material is smooth in surface appearance and few in defect, has high crystallinity similar to that of Mo2Ga2C, has application prospects in multiple fields such as energy storage and catalysis, and particularly promotes practical application of an MXene material in the field of new energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nano material preparation, in particular to a Mo2CT x Two-dimensional materials and their preparation methods and applications. Background Art

[0002] Two-dimensional transition metal carbide (MXene) materials have attracted much attention due to their unique physical and chemical properties. MXene family materials have the advantages of metallic conductivity or narrow bandgap semiconductor properties, open layered structure, weak interlayer forces and high specific surface area, which make them show broad application prospects in secondary ion batteries, catalysis, optics and other fields.

[0003] For Mo2CT x The traditional method for preparing two-dimensional materials generally uses strong acid and strong base etching methods. HF etching is the earliest and most widely used method for preparing MXene. Subsequently, related research on in-situ HF etching began to appear, namely NH4F+HCl etching or NH4HF2 etching. The mechanism they are based on is: + You can attack with the MA key, F - It forms soluble fluoride with free A-layer atoms, H + Participation in the formation of surface terminal groups also further promotes the etching reaction.

[0004] However, traditional MXene preparation methods often have some limitations. There are methods that require the use of hazardous reagents such as etching with strong acids or strong bases, and harsh methods such as molten salt etching at 700-1000°C using CuCl2 as an etchant, which not only poses safety hazards but may also have certain negative impacts on the environment. Secondly, existing preparation methods usually require complex equipment and long reaction cycles, resulting in low production efficiency and limited output. In addition, the yield of some preparation processes is low, which makes it difficult to meet the needs of large-scale applications. These problems not only increase the preparation cost of MXene materials, but also hinder their commercialization process to a certain extent. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a Mo2CT x Two-dimensional material and preparation method and application thereof. The preparation method provided by the present invention can prepare Mo2CT without using harsh conditions such as strong acid or strong base. x Two-dimensional material, high production efficiency.

[0006] The present invention provides a Mo2CT x A method for preparing a two-dimensional material comprises the following steps:

[0007] The Mo2Ga2C MAX material and ammonium fluoride are hydrothermally reacted to obtain Mo2CT x Two-dimensional materials;

[0008] The temperature of the hydrothermal reaction is 190° C. to 240° C., and the time of the hydrothermal reaction is 3 h to 36 h.

[0009] The Mo2CT provided by the present invention x A method for preparing two-dimensional materials, specifically a halogen hydrothermal preparation of Mo2CT x A two-dimensional material method can be used to etch Mo2Ga2C MAX material with ammonium fluoride to obtain Mo2CT x For two-dimensional materials, the key factor is the hydrothermal temperature. Conventional strong acid and strong base etching often does not exceed 100°C, because too high a temperature will cause higher safety hazards, and conventional strong acid or strong base etching can be successfully etched at a temperature below 100°C. Therefore, whether it is HF etching or in-situ HF etching, the temperature tends to be controlled at around 100°C. In the present invention, the temperature of the hydrothermal reaction of Mo2Ga2CMAX material and ammonium fluoride is 190°C~240°C, and the time is 3 h~36 h.

[0010] The inventors of this application creatively discovered that it is not necessary to follow the traditional H + Etching mechanism: Ammonium fluoride can be used to perform hydrothermal etching on Mo2Ga2C MAX materials at a temperature of 190℃~240℃. The pH of ammonium fluoride is mild, so the safety of etching at a temperature of 190℃~240℃ can also be guaranteed. In addition, the cost of ammonium fluoride is low. - Lower concentration, reduced risk of over-etching, better product uniformity, higher safety, less corrosion to equipment, and avoids the use of harsh conditions such as strong acid or strong alkali to prepare Mo2CT x Two-dimensional materials.

[0011] The present invention firstly conducts a hydrothermal reaction between the Mo2Ga2C MAX material and ammonium fluoride. Specifically, the present invention firstly mixes the Mo2Ga2C MAX material with water, then adds ammonium fluoride thereto to dissolve, and then conducts a hydrothermal reaction. In certain embodiments of the present invention, after the Mo2Ga2C MAX material and water are mixed, and after the ammonium fluoride is added thereto to dissolve, the dissolved oxygen is removed, specifically, a protective gas is introduced to remove the dissolved oxygen. The concentration of the Mo2Ga2C MAX material of the present invention is 50 mg / mL~150 mg / mL; the concentration of the ammonium fluoride is 1 mol / L~6 mol / L.

[0012] The lower the concentration of ammonium fluoride of the present invention, the longer the time for the hydrothermal reaction; the higher the concentration of ammonium fluoride, the shorter the time for the hydrothermal reaction. In some embodiments of the present invention, the concentration of ammonium fluoride is greater than 1 mol / L and less than 3 mol / L, and the time for the hydrothermal reaction is 12 h to 36 h. In other embodiments of the present invention, the concentration of ammonium fluoride is 3 mol / L to 6 mol / L, and the time for the hydrothermal reaction is 3 h to 12 h.

[0013] After the hydrothermal reaction, the present invention further comprises cooling the obtained reaction mixture, washing it to neutrality, and then drying it to obtain Mo2CT x Specifically, the present invention cools the obtained reaction mixture, washes the cooled material with water and ethanol, and then dries it to obtain Mo2CT x Two-dimensional material. The number of washing times of the present invention is 5 to 8 times; the drying is freeze drying, the freeze drying temperature is -90°C to -60°C, and the freeze drying time is 20 h to 30 h.

[0014] The Mo2Ga2C MAX material of the present invention is prepared by the following method: mixing molybdenum carbide nanopowder and metal gallium, heating and grinding to obtain a mixture; sintering the mixture to obtain the Mo2Ga2C MAX material; based on the amount of the molybdenum carbide nanopowder as 1 mol, the amount of the metal gallium is greater than 6 mol and less than 12 mol. The sintering of the present invention is carried out at a pressure of 10 Pa to 1000 Pa, the sintering temperature is 800°C to 1000°C, and the low vacuum sintering time is 24 h to 108 h.

[0015] The present invention also provides the Mo2CT described in any of the above technical solutions x Mo2CT prepared by the preparation method of two-dimensional materials x The present invention also provides the Mo2CT described in any of the above technical solutions. x Mo2CT prepared by the preparation method of two-dimensional materials x The application of two-dimensional materials in the fields of new energy, catalysis and optics, specifically in the fields of secondary ion batteries, supercapacitors or electrocatalysis. x Mo2CT obtained by the preparation method of two-dimensional materials x Two-dimensional materials have uniform interface structures, few surface adsorption groups, abundant active sites, and a wide range of applications, with potential commercial application value.

[0016] The present invention provides a Mo2CT xTwo-dimensional material and its preparation method and application. The Mo2CT provided by the present invention x The preparation method of the two-dimensional material is to etch Mo2Ga2C through a simple one-step hydrothermal reaction, and use ammonium fluoride with better safety and stability to etch MAX precursors in large quantities in one step to prepare Mo2CTx two-dimensional materials. The preparation process is simple, easy to mass produce, safe and reliable, and avoids the use of traditional harmful reagents HF. There is no need to introduce strong acids, strong bases or chemical intercalation agents; the obtained Mo2CT x The two-dimensional material has a smooth surface morphology, few defects, and has high crystallinity similar to Mo2Ga2C. It has application prospects in many fields such as energy storage and catalysis, especially promoting the practical application of MXene materials in the field of new energy. x The preparation method of two-dimensional materials is green, efficient and economical. It breaks through the existing technical bottleneck and can realize the large-scale production and commercial application of MXene materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Mo2CT prepared in Example 1 x X-ray diffraction spectra of two-dimensional materials;

[0018] Figure 2 Mo2Ga2C (a) and Mo2CT prepared in Example 1 x Scanning electron microscopy image of the two-dimensional material (b);

[0019] Figure 3 Mo2CT prepared in Example 1 x SEM EDS images of two-dimensional materials;

[0020] Figure 4 Mo2CT prepared in Example 1 x Transmission electron microscopy images of two-dimensional materials;

[0021] Figure 5 The Mo2CT prepared by adding 2 mol / L ammonium fluoride at 200°C for 1 day in Example 2 x X-ray diffraction spectra of two-dimensional materials;

[0022] Figure 6 The Mo2CT prepared by adding 4 mol / L ammonium fluoride at 220°C for 6 h in Example 3 x X-ray diffraction spectra of two-dimensional materials;

[0023] Figure 7 is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 1;

[0024] Figure 8is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 2;

[0025] Fig. 9 is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 3;

[0026] Fig.10 This is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 4. DETAILED DESCRIPTION

[0027] The invention discloses a Mo2CT x Two-dimensional materials and their preparation methods and applications. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0028] The present invention will be further described below in conjunction with embodiments:

[0029] Example 1

[0030] Weigh 10 g of Mo2Ga2C MAX powder sample, measure 100 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder to deionized water and pour into 50 mL of para-polyphenylene liner; then weigh 14.817 g of ammonium fluoride (4 mol / L) and add it to the above solution to mix, stir and dissolve, and pass argon to remove dissolved oxygen; place the above para-polyphenylene liner in a stainless steel reactor and put it in an oven at 220°C for 6 h; after the reaction is completed, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain Mo2CT x Two-dimensional materials.

[0031] like Figure 1 As shown, Figure 1 Mo2CT prepared in Example 1 x X-ray diffraction spectrum of the two-dimensional material. It can be seen from the figure that after etching by the above experimental method, the characteristic peaks of Mo2Ga2C at 34.2°, 37.4°, 40.0° and 42.6° are significantly reduced, proving that Ga is successfully etched out from the interlayer of Mo2Ga2C; Mo2CT x The two-dimensional material also shows characteristic peaks different from those of Mo2Ga2C. The (002) at 8.5° is significantly lower than 9.9° of Mo2Ga2C, and the interlayer spacing increases, further proving the success of etching.

[0032] like Figure 2 As shown, Figure 2 Mo2Ga2C (a) and Mo2CT prepared in Example 1 x Scanning electron microscope image of the two-dimensional material (b). It can be seen from the figure that Mo2CT x The two-dimensional material has a smooth surface morphology, few defects, and high crystallinity similar to Mo2Ga2C.

[0033] like Figure 3 As shown, Figure 3 Mo2CT prepared in Example 1 x SEM EDS image of two-dimensional materials. Mo2CTx two-dimensional materials contain a small amount of F; it is worth mentioning that the atomic ratio of Ga element is less than 1%.

[0034] like Figure 4 As shown, Figure 4 Mo2CT prepared in Example 1 x Transmission electron microscopy images of two-dimensional materials show that there is no obvious change in interlayer crystallinity; Figure 5 The atomic ratio of Mo to C obtained from the TEM EDS of the surface structure is about 1:2. Combined with the results of the X-ray diffraction spectrum, it is confirmed that Mo2CT was successfully prepared. x Two-dimensional materials.

[0035] Example 2

[0036] Weigh 200 mg of Mo2Ga2C MAX powder sample, measure 20 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder into deionized water and pour into 50 mL of para-polyphenylene lining; then weigh 1.483 g of ammonium fluoride (2 mol / L) and add it to the above solution to mix, stir and dissolve, and pass argon to remove dissolved oxygen; place the above para-polyphenylene lining in a stainless steel reactor and put it in an oven at 200°C to react for 1 day; after the reaction is completed, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain Mo2CTx two-dimensional material.

[0037] like Figure 5 As shown, Figure 5 The Mo2CT prepared by adding 2 mol / L ammonium fluoride at 200°C for 1 day in Example 2 x X-ray diffraction spectrum of the two-dimensional material. It can be seen from the figure that the characteristic peak of Mo2Ga2C is significantly reduced after etching, and the (002) in the material is reduced to 8.5° compared to 9.9° of Mo2Ga2C, and the interlayer spacing is increased, which further proves the success of etching.

[0038] Example 3

[0039] Weigh 1 g of Mo2Ga2C MAX powder sample, measure 50 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder to deionized water and pour into 100 mL of para-polyphenylene liner; then weigh 7.408 g of ammonium fluoride (4 mol / L) and add it to the above solution to mix, stir and dissolve, and then pass argon to remove dissolved oxygen; place the above para-polyphenylene liner in a stainless steel reactor and put it in an oven at 220°C for 6 h; after the reaction, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain Mo2CT x Two-dimensional materials.

[0040] like Figure 6 As shown, Figure 6 The Mo2CT prepared by adding 4 mol / L ammonium fluoride at 220°C for 6 h in Example 3 x In the X-ray diffraction spectrum of the two-dimensional material, the characteristic peak of Mo2Ga2C is significantly reduced, proving that Ga is successfully etched out from the interlayer of Mo2Ga2C and the etching is successful; the (002) of the prepared material is also significantly reduced compared to Mo2Ga2C, and the interlayer spacing is increased; the surface morphology shows crystallinity similar to that of Mo2Ga2C; the Ga element signal is difficult to detect in the element distribution map, further confirming the successful etching.

[0041] Comparative Example 1

[0042] Weigh 500 mg of Mo2Ga2C MAX powder sample, measure 20 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder into deionized water and pour into 50 mL of para-polyphenylene lining; then weigh 1.482 g of ammonium fluoride (2 mol / L) and add it to the above solution to mix, stir and dissolve, and pass argon to remove dissolved oxygen; place the above para-polyphenylene lining in a stainless steel reactor and put it in an oven at 220°C for reaction for 3 h; after the reaction is completed, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain the reactant.

[0043] The material obtained in Comparative Example 1 was analyzed using X-ray diffraction technology to obtain its X-ray diffraction spectrum, as shown in FIG. Figure 7 As shown, Figure 7 is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 1; Figure 7 It can be seen that although there is an obvious Mo2CT xThe characteristic peaks of MXenes appear, but the characteristic peaks of Mo2Ga2C still exist, proving that Mo2Ga2C has not been completely successfully etched.

[0044] Comparative Example 2

[0045] Weigh 200 mg of Mo2Ga2C MAX powder sample, measure 20 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder into deionized water and pour into 50 mL of para-polyphenylene lining; then weigh 6.419 g (6 mol / L) of ammonium chloride and add it to the above solution to mix, stir and dissolve, and pass argon to remove dissolved oxygen; place the above para-polyphenylene lining in a stainless steel reactor and put it in an oven at 220°C to react for 1 day; after the reaction is completed, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain the reactant.

[0046] like Figure 8 As shown, Figure 8 This is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 2. After etching in the above manner, the (002) peak shifts to the left, but the characteristic peak of Mo2Ga2C still exists, indicating that the prepared material is not completely etched; its surface morphology is not significantly different from that of Mo2Ga2C, and the Ga element signal is strong in the element distribution diagram, indicating that it is not completely etched.

[0047] Comparative Example 3

[0048] Weigh 200 mg of Mo2Ga2C MAX powder sample, measure 20 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder into deionized water and pour into 50 mL of para-polyphenylene lining; then weigh 17.629 g (9 mol / L) of ammonium bromide and add it to the above solution, stir to dissolve and pass argon to remove dissolved oxygen; place the above para-polyphenylene lining in a stainless steel reactor and put it in an oven at 220°C to react for 1 day; after the reaction, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain the reactant.

[0049] like Fig. 9 As shown, Fig. 9 This is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 3. After etching in the above manner, the (002) peak almost does not appear, and the characteristic peak of Mo2Ga2C still exists, indicating that the prepared material is not completely etched; its surface morphology is not significantly different from that of Mo2Ga2C, and the Ga element signal is strong in the element distribution diagram, indicating that it is not completely etched.

[0050] Comparative Example 4

[0051] Weigh 200 mg of Mo2Ga2C MAX powder sample, measure 20 mL of deionized water and use an air gun to pass argon to remove dissolved oxygen, add Mo2Ga2C powder into deionized water and pour into 50 mL of para-polyphenylene liner; then weigh 2.9632 g of ammonium fluoride (4 mol / L) and add it to the above solution to mix, stir and dissolve, and pass argon to remove dissolved oxygen; place the above para-polyphenylene liner in a stainless steel reactor and put it in an oven at 120°C to react for 2 days; after the reaction is completed, naturally cool to room temperature, repeatedly wash with deionized water and anhydrous ethanol until neutral, and use freeze-drying technology to dry at -82°C for 24 hours to obtain the reactant.

[0052] like Fig.10 As shown, Fig.10 This is the X-ray diffraction spectrum of the reactant obtained in Comparative Example 4. After etching in the above manner, it can be seen that the (002) peak at 10° does not shift to the left, indicating that the etching has failed.

[0053] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A Mo2CT x A method for preparing a two-dimensional material, characterized in that: The following steps are involved: The Mo2Ga2C MAX material and ammonium fluoride are hydrothermally reacted to obtain Mo2CT x Two-dimensional materials; The temperature of the hydrothermal reaction is 180° C. to 240° C., and the time of the hydrothermal reaction is 3 h to 36 h.

2. Mo2CT according to claim 1 x A method for preparing a two-dimensional material, characterized in that: The concentration of the ammonium fluoride is 1 mol / L to 6 mol / L.

3. Mo2CT according to claim 1 x A method for preparing a two-dimensional material, characterized in that: The concentration of ammonium fluoride is greater than 1 mol / L and less than 3 mol / L, and the time of the hydrothermal reaction is 12 h to 36 h; or, The concentration of the ammonium fluoride is 3 mol / L to 6 mol / L, and the time of the hydrothermal reaction is 3 h to 12 h.

4. Mo2CT according to claim 1 x A method for preparing a two-dimensional material, characterized in that: The concentration of the Mo2Ga2C MAX material is 50 mg / mL~150 mg / mL.

5. Mo2CT according to claim 1 x A method for preparing a two-dimensional material, characterized in that: After the hydrothermal reaction, the method further includes freeze-drying the material after the hydrothermal reaction; The freeze-drying temperature is -90°C to -60°C, and the freeze-drying time is 20 h to 30 h.

6. The Mo2CT according to any one of claims 1 to 5 x A method for preparing a two-dimensional material, characterized in that: The Mo2Ga2C MAX material is prepared by the following method: Grinding molybdenum carbide nanopowder and metal gallium at 65° C. to 75° C. to obtain a mixture; The mixture is vacuum sintered to obtain Mo2Ga2C MAX material.

7. Mo2CT according to claim 6 x A method for preparing a two-dimensional material, characterized in that: Based on 1 mol of the molybdenum carbide nanopowder, the amount of the metal gallium is greater than 6 mol and less than 12 mol.

8. Mo2CT according to claim 6 x A method for preparing a two-dimensional material, characterized in that: The sintering is carried out under a pressure of 10 Pa to 1000 Pa; the sintering temperature is 800° C. to 1000° C., and the sintering time is 24 h to 108 h.

9. The Mo2CT according to any one of claims 1 to 8 x Mo2CT prepared by the preparation method of two-dimensional materials x Two-dimensional materials.

10. The Mo2CT according to any one of claims 1 to 8 x Mo2CT prepared by the preparation method of two-dimensional materials x Application of two-dimensional materials in secondary ion batteries, supercapacitors or electrocatalysis.